Mannose-Coated Reconstituted Lipoprotein Nanoparticles for the Targeting of Tumor-Associated Macrophages: Optimization, Characterization, and In Vitro Evaluation of Effectiveness - Akpedje S. Dossou; Morgan E. Mantsch; Ammar Kapic; William L. Burnett; Nirupama Sabnis; Jeffery L. Coffer; Rance E. Berg; Rafal Fudala; Andras G. Lacko (MDPI AG, 2023)
Reconstituted high-density lipoprotein nanoparticles (rHDL NPs) have been utilized as delivery vehicles to a variety of targets, including cancer cells. However, the modification of rHDL NPs for the targeting of the pro-tumoral tumor-associated macrophages (TAMs) remains largely unexplored. The presence of mannose on nanoparticles can facilitate the targeting of TAMs which highly express the mannose receptor at their surface. Here, we optimized and characterized mannose-coated rHDL NPs loaded with 5,6-dimethylxanthenone-4-acetic acid (DMXAA), an immunomodulatory drug. Lipids, recombinant apolipoprotein A-I, DMXAA, and different amounts of DSPE-PEG-mannose (DPM) were combined to assemble rHDL-DPM-DMXAA NPs. The introduction of DPM in the nanoparticle assembly altered the particle size, zeta potential, elution pattern, and DMXAA entrapment efficiency of the rHDL NPs. Collectively, the changes in physicochemical characteristics of rHDL NPs upon the addition of the mannose moiety DPM indicated that the rHDL-DPM-DMXAA NPs were successfully assembled. The rHDL-DPM-DMXAA NPs induced an immunostimulatory phenotype in macrophages pre-exposed to cancer cell-conditioned media. Furthermore, rHDL-DPM NPs delivered their payload more readily to macrophages than cancer cells. Considering the effects of the rHDL-DPM-DMXAA NPs on macrophages, the rHDL-DPM NPs have the potential to serve as a drug delivery platform for the selective targeting of TAMs.